Insights Into the Role of the Lung Virome During Respiratory Viral Infections - Porto, Bárbara N. (Frontiers in Immunology, 2022)
The virome constitutes the viral component of the microbiome and it consists of the genomes of all the viruses that inhabit a particular region of the human body, including those that cause acute, persistent or latent infection, and retroviral elements integrated to host chromosomes. The human virome is composed by eukaryotic viruses, bacteriophages and archaeal viruses. The understanding of the virome composition and role on human health has been delayed by the absence of specific tools and techniques to accurately characterize viruses. However, more recently, advanced methods for viral diagnostics, such as deep sequencing and metagenomics, have allowed a better understanding of the diverse viral species present in the human body. Previous studies have shown that the respiratory virome modulates the host immunity and that, since childhood, the human lung is populated by viruses for whom there is no disease association. Whether these viruses are potentially pathogenic and the reason for their persistence remain elusive. Increased respiratory viral load can cause exacerbation of chronic pulmonary diseases, including COPD, cystic fibrosis, and asthma. Moreover, the presence of resident viral populations may contribute to the pathogenesis of community-acquired respiratory virus infections. In this mini review, I will discuss the recent progress on our understanding of the human lung virome and summarize the up-to-date knowledge on the relationships among community-acquired respiratory viruses, the lung virome and the immune response to better understand disease pathophysiology and the factors that may lead to viral persistence.